US Defence Strategy from Vietnam to Operation Iraqi Freedom: Military Innovation and the New American War of War, 1973-2003, 1st edition - Tomes, Robert R. (Routledge, 2020)
US Defence Strategy from Vietnam to Operation Iraqi Freedom examines the thirty-year transformation in American military thought and defence strategy that spanned from 1973 through 2003.